-3/4 y + 1/4 = 1/2
3/4y = -(1/2 - 1/4)
3/4 y = -1/4
3y = -1
y = -1/3
0.4a + 0.4(2) = 2
0.4a = 2 - 0.8
0.4a = 1.2
a = 3
2007-01-30 14:30:27
·
answer #1
·
answered by car of boat 4
·
0⤊
0⤋
Solve means to find the value of y (in this case) which satisfies the equation:
1)
- 3/4y + 1/4 = 1/2
-3/4y = 1/4
y = -1/3
2)
0.4 { a + 2 } = 2
a + 2 = 5
a = 3
2007-01-30 22:30:37
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
question 1.
- 3/4y + 1/4 = 1/2
-3/4y = 1/2 - 1/4
lcf(4, 2) = 4
-3/4y = 2/4 - 1/4
-3y = 1
y = -1/3
><
question 2.
0.4 { a + 2 } = 2
0.4a + 0.8 = 2
0.4a = 2 - 0.8
0.4a = 1.2
a = 3
><
2007-01-30 22:43:28
·
answer #3
·
answered by aeiou 7
·
0⤊
0⤋
to solve each question, you have to find out the answer for the variable
the variable is the term that is unknown
question 1:
-3/4y + 1/4 = 1/2
first you move the 1/4 to the other side..when it goes to the other side, its a MINUS 1/4
-3/4y = 1/2 - 1/4
-3/4y = 1/4
now you divide both sides by -3/4 to isolate for y
y = (1/4)/(-3/4)
therefore, y = -1/3
question 2:
same deal as question 1
0.4(a + 2) = 2
divide both sides by 0.4
(a + 2) = 5
a = 5 - 2
therefore, a = 3
:)
2007-01-30 22:29:58
·
answer #4
·
answered by Bored 2
·
0⤊
0⤋
1) Subtract 1/4 from both sides.
-3/4y=1/4 >>> Divide by -3/4, or multiply by -4/3, same thing.
y=-3/12 = -1/4
2) Multiply by 0.4, or 4/10
a+2 = 8/10 = 4/5
Subtract 2 from both sides.
a= (4/5) - 2 = -6/5 = -1.2
2007-01-30 22:30:29
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
1.-3/4y+1/4=1/2
=>-3/4y+1/4-1/4=1/2-1/4 [deducting 1/4 from both sides]
=>-3/4y=1/4
=>(-3/4y)/-3/4=1/4/-3/4
[dividing both sides by- 3/4]
=>y=-1/3
2.0.4(a+2)=2
=>10*0.4(a+2)=10*2 [multiplying both sides by 10]
=>4(a+2)=20
=>4a+8=20
=>4a+8-8=20-8 [subtracting 8 from both sides]
=>4a=12
=>4a/4=12/4 [dividing both sides by 4]
=>a=3
[
2007-01-30 22:32:56
·
answer #6
·
answered by alpha 7
·
0⤊
0⤋
3/4y + 1/4 = 1/2
1/2y = 1/4
1/2y(2) = 1/4(2)
y = 1/2
0.4(a + 2) = 2
0.4a + 28/10 = 2
0.4a = --0.8
a = --0.32
i think thats it
i did it in my head
2007-01-30 22:36:45
·
answer #7
·
answered by st jimmy 2
·
0⤊
0⤋
3/4y + 1/4 = 1/2
3/4y = 1/4
y = 1/4 / 3/4
y = .333...
0.4(a+2) = 2
.4a + .8 = 2
.4a = 1.2
a = 1.2/.4
a = 3
do you get this?
2007-01-30 22:28:39
·
answer #8
·
answered by the_akbash 1
·
0⤊
0⤋
-3/4y+1/4=1/2
-3/4y=1/2-1/4
-3/4y=-3/4
2007-01-30 22:31:21
·
answer #9
·
answered by coolvolcano 1
·
0⤊
0⤋
1.)
(-3/4)y + (1/4) = (1/2)
Multiply everything by 4
-3y + 1 = 2
-3y = 1
y = (-1/3)
------------------------------
2.)
.4(a + 2) = 2
a + 2 = 2/(.4)
a + 2 = 20/4
a + 2 = 5
a = 3
2007-01-30 23:08:16
·
answer #10
·
answered by Sherman81 6
·
0⤊
0⤋